2022
DOI: 10.2147/ijgm.s372038
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Inflammation and Coagulation Markers with the Incidence of Deep Vein Thrombosis in Cancer Patients with High Risk of Thrombosis

Abstract: Background Deep vein thrombosis (DVT) is a common complication and the second leading cause of death in cancer patients. Pro-inflammatory stimuli in the cancer microenvironment induce nuclear factor kappa B (NF-κB) signaling pathway that plays an integral role in immunothrombosis mechanism. Objective To investigate the role of inflammatory and coagulation biomarkers in the development of DVT in cancer patients with high risk of thrombosis (Khorana score ≥2). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Our more detailed analysis revealed that for strokes associated with LPC cancers, but neither breast and prostate cancers nor bacterial endocarditis, steep increases in the average number of ischemic territories depending on both higher CRP and LDH levels were characteristic. Our finding corresponds quite well to observations that CRP positively correlates with D-dimers in paraneoplastic coagulopathy associated with venous thrombosis 43 and higher D-dimer levels in turn with a higher number of ischemic territories in cancer-associated stroke. 19 , 47 In summary, our findings reported here as well as previous reports are compatible with the hypothesis that the extent to which certain tumors, especially LPC cancer, induce inflammation dictates the activation of coagulation and thereby multiple ischemic events typical for paraneoplastic ischemic stroke.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our more detailed analysis revealed that for strokes associated with LPC cancers, but neither breast and prostate cancers nor bacterial endocarditis, steep increases in the average number of ischemic territories depending on both higher CRP and LDH levels were characteristic. Our finding corresponds quite well to observations that CRP positively correlates with D-dimers in paraneoplastic coagulopathy associated with venous thrombosis 43 and higher D-dimer levels in turn with a higher number of ischemic territories in cancer-associated stroke. 19 , 47 In summary, our findings reported here as well as previous reports are compatible with the hypothesis that the extent to which certain tumors, especially LPC cancer, induce inflammation dictates the activation of coagulation and thereby multiple ischemic events typical for paraneoplastic ischemic stroke.…”
Section: Discussionsupporting
confidence: 91%
“… 28 , 41 In addition, in paraneoplastic venous thrombosis, D-dimers strongly correlate with inflammatory blood markers. 43 Interestingly, high blood levels of some epithelial glycoproteins commonly used as tumor markers for carcinomas, that is, CA-125 aka Mucin-16, are associated with paraneoplastic ischemic stroke. 44 Experimentally, injecting these proteins into the circulation directly activates coagulation through adhesion-dependent, reciprocal activation of neutrophils and platelets.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is formed a self-sustaining vicious pathogenetic circle of pathological process, which becomes independent of the damage factors at a certain stage of development. This process, called "thromboinflammation" or "immunothrombosis" is considered today as a universal pathogenetic mechanism of many acute and chronic diseases [1,5,8,10,11]. The results of the present study showed that the risk of hypercoagulation increases with increasing severity of SIR.…”
Section: Resultsmentioning
confidence: 47%
“…Cancer patients also experience an increased affinity for thrombosis and concurrent venous inflammation ( Setiawan et al, 2022 ). As an acquired thrombophilia, cancer inflammation in the microenvironment induces a pro-inflammatory response including the release of Tumor Necrosis Factor Alpha (TNF-alpha) and cytokines including interleukins 1a, 6, 17, and 18 ( Setiawan et al, 2022 ). This inflammation is responsible for widespread endothelial cell damage and concurrent risk of thrombotic episodes.…”
Section: Inflammation-induced Coagulationmentioning
confidence: 99%